Earth, gender and food security: Maria Zaloumis" journey of feminising Agric-business in Zambia - Mwale, Nelly (HTS teologiese studies, 2023)
This article explores the interconnectedness of the earth, gender and food security in the Zambian context using the narrative of Maria Zaloumis (a female Zambian farmer) in the public sphere. It draws on a narrative research design by the restorying of Maria’s trajectory in Agric-business as informed by the African ecofeminist theory. The study shows that Maria was described as an emerging young farmer and an emblem of female entrepreneurship. Her trajectory mirrored the intersection of the earth, gender and food security through her portrayal as a woman who endured life tragedies of losing a child, and being a victim of gender-based violence in her marriage. She drew inspiration from her mother (venturing into farming was linked to her mother), the earth (farming was an outlet for healing from her marital challenges) and religion (attributed her success to God as a member of the Baptist church). Maria’s account which resonates with the injustice suffered by the earth and shared by women through the environmental crises affirms that in the midst of suffering, women could still contribute to food security by turning a crisis into an opportunity and fostering a life-affirming theology.Contribution: The article contributes to scholarship on the earth, gender and food security by bringing to the fore the ways in which women have contributed to changing the Agric-business landscape through the intersection of the earth, gender and religion from the Zambian context. It also adds a new perspective to women’s empowerment and the preservation and stewardship of mother earth.